Does body mass index influence behavioral regulations, dispositional flow and social physique anxiety in exercise setting? - (:unkn) unknown (Journal of Sport Science and Medicine, 2016)
The purpose of this study was to examine differences in behavioral regulations, dispositional flow, social physique anxiety of exercisers in terms of body mass index (BMI). 782 university students participated in this study. Dispositional Flow State Scale-2, Behavioral Regulations in Exercise Questionnaire-2, Social Physique Anxiety Scale and Physical Activity Stages of Change Questionnaire were administered to participants. After controlling for gender, analysis indicated significant differences in behavioral regulations, dispositional flow and social physique anxiety of exercise participants with regards to BMI. In summary, the findings demonstrate that normal weighted participants exercise for internal reasons while underweighted participants are amotivated for exercise participation. Additionally, participants who are underweight had higher dispositional flow and lower social physique anxiety scores than other BMI classification. © Journal of Sports Science and Medicine.
Keywords: Behavioral regulations; Body mass index; Dispositional flow; Self-determination theory; Social physique anxiety